Pengaruh Pelatihan Terhadap Kinerja Melalui Motivasi (Studi pada Karyawan PT Pos Indonesia Persero Malang) - Fitriana Damayanti; Armanu Thoyib (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research was conducted in PT Pos Indonesia (Persero) Malang. Human resources is a key principal in the company to stay afloat in an era of global competition. In addition, human resources is one key to the success of a company. Training is one way to improve the knowledge and skills of human resources. With the training, motivation of employees is expected to increase and therefore contributes to the performance of the employees and indirectly the performance of the company will also increase.The design of the research is explanatory research (explanation). In this study describes the relationship between the study variables and test hypotheses that have been formulated. The sample used by 55 respondents. Methods of data collection in this study was measured using a questionnaire using a Likert scale with a five-point scale. While the analysis of the data using descriptive analysis techniques and path analysis to determine the effect of training on performance through employee motivation PT Pos Indonesia (Persero) Malang are processed using SPSS 15.0 for windows. The results of this study are as follows: (1) Work Motivation (Z) directly and significantly affect employee performance (Y) in PT Pos Indonesia (Persero) Malang, (2) Training (X) directly and significantly affect the performance Employees (Z) in PT Pos Indonesia (Persero) Malang, (3) Employment Training (X) directly and significantly affect the Employee Motivation (Z) in PT Pos Indonesia (Persero) Malang (4) Training and indirectly influence significantly to the Employee Performance (Y) through the Work Motivation (Z) in PT Pos Indonesia (Persero) Malang.This suggests that PT Pos Indonesia (Persero) Malang has been implemented with both job training as a way to motivate employees so as to improve performance.Keywords: Job Training, Work Motivation, Employee Performance